Atlas for computing mathematical funtions an illustrated guidebook for proctitioners with programs in Fortran 90 and Mathematica - Thompson, William J. (William Jackson) (John Wiley & Sons, 1997)
Introducing a comprehensive book and CD-ROM for visualizing and computing special functions. Here is an invaluable reference and learning guide to more than 150 special functions of applied mathematics, statistics, physics, chemistry, computer science, and engineering. The Atlas contains over 700 graphics of the functions, which readers can also create by using the annotated Mathematica files provided. It offers complete, consistent instructions and test values for computing the functions accurately and efficiently with the full Fortran-90 source programs on the CD-ROM, which is both Windows and Macintosh compatible. With extensive references and indexing, this integrated package is superbly designed and easy to use--ideal for anyone who works with special functions.